Pendidikan Islam Masa Khulafaur Rasyidin dan Perannya dalam Pengembangan Pendidikan Islam - Nur Munawaroh; Muhammad Kosim (Program studi Keagamaan Islam, 2021)
This paper aims to determine the development of Islamic education during the Khulafaur Rasyidin period. This type of research uses library research with data collection methods through the documentation method. The results of this study include: First, Khulafa Rasyidin means the replacement of a scholarly Apostle. The originators of the name Khulafa Rashidin were the Muslims who were closest to the Prophet after his death. The four figures after the death of the Apostle were people who always accompanied the Apostle when he was a leader and in carrying out his duties. These four figures are Abu Bakr as-Siddiq, Umar bin Khattab, Uthman bin Affan and Ali bin Abi Talib. The period of Khulafaur Rashidin lasted for 32 years. Second, there are many developments in Islamic education during this caliphate, which is expected to be an example and an illustration of organizing Islamic education in this millennial era